'The group with the flag': Mine hostels as contested institutions - James, Wilmot G. (My University, 1989)
A majority—almost 99 per cent—of African miners live in mine hostels. These are single-sex quarters located close to mine shafts,and they service the labour needs of individual mines. In the past they have also been called compounds, to refer to the time when the mine quarters were basic and primitive facilities, with large rooms in some instances accommodating up to 90 miners in their public space, no private ablution, toilet facilities, electricity, and minimal, modest service provision. Corporate embarrassment about compound life, brought about in part by a number of academic studies published in the 1970s motivated the mining houses to reform and improve the mine residence, and substantial sums of money were pumped into upgrading, and, as Merle Lipton put it, ameliorating the conditions of mine life. Room size and propinquity were reduced, private ablution and toilet facilities provided, electricity was supplied, and recreation and bar facilities became part of the hostel environment. The compounds were modernised quite considerably in the 1970s, and part of the modernisation was a change also in nomenclature; they became known as hostels, a term denoting mass residence, but free of more or less guaranteed a physically competent work force. It is also true that, since it was first put in place almost a century ago, the compound has been a most important device by which the mine labour force has been sheltered from politics. During the 1980s, as this chapter will show, the mine labour force was irreversibly incorporated into politics, and took a leading role in the politics of the Congress of South African Trade Unions (COSATU), the largest union federation in the nation today.
African Studies Seminar series. Paper presented February, 1989
Keywords: Strikes and lockouts. Miners. South Africa; Miners. South Africa. Social conditions; Miners. Political activity. South Africa